The development of Metabolic Syndrome in patients with late onset Hypogonadism (Research, Society and Development, 2024)
Introduction: The reduction in serum testosterone levels with age can be associated with an increase in body fat and a worsening of endocrine-metabolic parameters, culminating in metabolic syndrome and hypogonadism. Objective: The aim of this study was to evaluate the clinical, epidemiological and pathophysiological aspects of metabolic syndrome resulting from late onset hypogonadism, building on knowledge based on case reports and knowledge based on the literature. Materials and Methods: This is an integrative literature review on the general clinical characteristics of metabolic syndrome induced by reduced testosterone levels. The PICO strategy was used to develop the guiding question. In addition, the descriptors "Metabolic Syndrome"; "Late Hypogonadism"; "Gonadal Disorders" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: A significant proportion of the articles showed that there is an association between low testosterone levels, characteristic of late-onset hypogonadism, and the development of metabolic syndrome, especially in patients aged between 30 and 50. The management of the combination of these endocrine conditions must be planned and individualized in order to offer the best prognosis for the patient. Conclusion: The bidirectionality between the pathophysiological mechanisms of the diseases is extremely important for an integrative understanding of them, as well as the aspects that involve therapy, and is fundamental for patients to receive the best care.